Estimation of the emission altitude of pulsating aurora using the five-wavelength photometer - Yuki Kawamura; Keisuke Hosokawa; Satonori Nozawa; Yasunobu Ogawa; Tetsuya Kawabata; Shin-Ichiro Oyama; Yoshizumi Miyoshi; Satoshi Kurita; Ryoichi Fujii (Earth, Planets and Space, 2020)
Abstract Using a ground-based five-wavelength photometer, which has been operative in Tromsø, Norway since February 2017, we have statistically analyzed the lifetime of O(1S) to reveal the emission altitude of pulsating aurora (PsA). For the statistics, we have extracted intervals of PsA using an EMCCD all-sky imager on 37 nights during 3 months from January to March, 2018. By performing a cross-correlation analysis between the time-series of 427.8 nm (N2 + first negative band) and 557.7 nm oxygen emissions, we derived the distribution of the lifetime of O(1S). The mean of the lifetime is 0.67 s and the mode is around 0.7 s. We estimated the emission altitude of PsA using the lifetime of O(1S) and then carried out a case study, in which we compared the temporal variations of the emission altitude with the peak height of E region ionization obtained from the simultaneous observation of the EISCAT UHF radar. We confirmed an overall agreement between the two parameters, indicating the feasibility of using the current method for estimating the energy of precipitating electrons causing PsA. In addition, we have derived the statistical characteristics of the emission altitude of PsA. The result shows that the emission altitude becomes lower in the morning side than in the midnight sector, which indicates that the energy of PsA electrons is higher in the later MLT sector. Especially, there is a decrease of the emission altitude at around 06 MLT. However, the model calculation infers that the energy of cyclotron resonance between magnetospheric electrons and whistler-mode chorus waves does not change so much depending on MLT. This implies that the observed change of the emission altitude cannot be explained only by the MLT dependence of resonance energy.